ÐšÑ€Ñ–Ð¾ÐºÐ¾Ð½ÑÐµÑ€Ð²ÑƒÐ²Ð°Ð½Ð½Ñ Ñ„Ñ€Ð°Ð³Ð¼ÐµÐ½Ñ‚Ñ–Ð² cÐµÐ»ÐµÐ·Ñ–Ð½ÐºÐ¸ ÑÐ²Ð¸Ð½ÐµÐ¹ Ñƒ Ð¿Ñ€Ð¸ÑÑƒÑ‚Ð½Ð¾ÑÑ‚Ñ– Ð¿Ð¾Ð»Ñ–ÐµÑ‚Ð¸Ð»ÐµÐ½Ð¾ÐºÑÐ¸Ð´Ñ–Ð² - Galchenko, S. E. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2006)
Effect of cryopreservation on bioenergetic indices of porcine spleen fragments was studied. Normalisation of endogenous respiration and its coupling with oxidative phosphorylation to the 60th incubation minute and its significant decrease to the 120th minute were found both in the control and cryopreserved fragments of porcine spleen. The intensity of lipid peroxidation in cryopreserved fragments statistically and significantly exceeds the control value.